Paradise Lost?: State Failure in Nepal - Riaz, Ali; Basu, Subho (Lexington Books, 2007)
Paradise Lost examines the state-society relationships in Nepal and demonstrates that the nature of the state, disjuncture between the state and the society, and the rupture of the ideological hegemony of the ruling class of Nepal have created a situation where existing institutional frameworks are disintegrating and the state is rapidly unraveling. Dr. Ali Riaz and Dr. Subho Basu analyze the roles of ethnicity, identity, and deprivation, in engendering discontent and the rise of the Maoists as a formidable political force. Mindful of the geo-strategic importance of the country, this book contextualizes these domestic developments within the post-9/11 global world. Jointly authored by a political scientist and a historian this book brings together structural and historical perspectives. Written in an engaging language, Paradise Lost? will appeal to political scientists, historians, sociologists, and those interested in current affairs.